Efeitos modulatórios da acupuntura sobre a hipertensão arterial, o pulso radial e o estresse oxidativo em pacientes em uso de drogas anti-hipertensivas - Vasconcelos, Enilde Coutinho Rodrigues Sales (2016)
The Hypertension is a major cause of death in Brazil, reaching its prevalence around 30% of the adult population. In the world, it is related to more than 7 million deaths a year and is considered the main risk factor for cardiovascular diseases and stroke. Acupuncture is a form of prevention and treatment that is part of the traditional Chinese medicine; it is a form of therapy that seeks treatment by applying stimuli through needles inserted into the skin at specific points called Acupoints, resulting in the release of several neurotransmitters with the purpose of balancing the Yin and Yang energies that are part of its theoretical foundation. Free radicals are highly reactive and unstable chemical species by the presence of an unpaired electron in the last layer. Naturally formed during the metabolic process, but causing unbalance when in excess, it can cause cell damage and various diseases. To evaluate the action of Ac in SAH and Oxidative Stress (OS), we conducted a prospective, controlled study, comparing two groups of hypertensive patients at the HUWC’s Cardiology Clinic, who were in use of antihypertensive drugs for at least two years . Each group consisted of ten patients analyzed for ten weeks; the first group received a weekly Ac session at specific points, who were already used in other studies for the treatment of hypertension. The second group wasn’t treated with Ac, only making use antihypertensive drugs. All twenty patients remained in the supine position for 30 minutes and underwent measurement of BP and bilateral radial pulse before and after they had rested. We used the dosages of Glutathione (GSH) and malondialdehyde (MDA) to evaluate the OS and laboratory tests of blood glucose, transaminases, urea and creatinine, to evaluate hepatic, renal and metabolic functions. The data was statistically analyzed by ANOVA / Dunnett and Kolmorogov tests, showing a p value of less than 0,05.. In this study there was no change in blood pressure levels of patients treated with Ac, according to the statistical method used. The measured pulse showed a decrease (p <0.01); there was no change of MDA levels measured by TBARS of patients undergoing treatment. There was an increase in GSH levels (p <0.05) and decreased levels of AST and urea; there was no change in blood glucose tests, ALT and Creatinine. This study showed in conclusion, that Ac exerted a protective effect on the OS, decreases hepatic and renal effects of hypertension and has also promoted the redution of the radial pulse. Keywords: Arterial hypertension. Acupuncture. Oxidative stress.